Genome sequencing of Rhinorhipus Lawrence exposes an early branch of the Coleoptera - Kusy, Dominik; Motyka, Michal; Andujar, Carmelo; Bocek, Matej; Masek, Michal; Sklenarova, Katerina; Kokas, Filip; Bocakova, Milada; Vogler, Alfried P; Bocak, Ladislav (Frontiers in zoology, 2018)
BACKGROUND: Rhinorhipidae Lawrence, 1988 is an enigmatic beetle family represented by a single species, Rhinorhipus tamborinensis Lawrence, 1988, from Australia, with poorly established affinities near the superfamily Elateroidea (click beetles, soldier beetles and fireflies) or the more inclusive series (infraorder) Elateriformia. Its evolutionary position may inform the basal relationships of the suborder Polyphaga, the largest clade of Coleoptera. RESULTS: We analyzed four densely sampled DNA datasets of major coleopteran lineages for mitogenomes, rRNA genes and single copy nuclear genes. Additionally, genome sequencing was used for incorporation of R. tamborinensis into a set of 4220 orthologs for 24 terminals representing 12 polyphagan superfamilies. Topologies differed to various degrees, but all consistently refute the proposed placement of Rhinorhipidae in Elateroidea and instead indicate either sister relationships with other Elateriformia, frequently together with Nosodendridae, another divergent small family hitherto placed in Derodontoidea, or in an isolated position among the deepest lineages of Polyphaga. The phylogenomic analyses recovered Rhinorhipus in a sister position to all other Elateriformia composed of five superfamilies. Therefore, we erect the new superfamily Rhinorhipoidea Lawrence, 1988, stat. Nov., with the type-family Rhinorhipidae. The origins of the Rhinorhipidae were dated to the Upper Triassic/Lower Jurassic at the very early phase of polyphagan diversification. CONCLUSIONS: Thus, Rhinorhipidae adds another example to several recently recognized ancient relict lineages which are interspersed within contemporaneous hugely species-rich lineages of Coleoptera.
Keywords: Molecular phylogeny; Triassic; New superfamily; Rhinorhipidae; Phylotranscriptomics; Elateriformia